Maximizing WhatsApp Group for Students Group Presentation in Learning English Online - Marisa Fran Lina (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2021)
WhatsApp Group (WAG) is one favorite choice for an online learning platform in this Covid-19 pandemic era. It is accessible, quite cheap, and user-friendly. Meanwhile, one of the activities in online English learning via WAG is a class group division named Students' Group Presentation (SGP). The aim is to train the students to manage online learning in their classes confidently. Therefore, this study is to describe the lecturer's experience in handling SGP through WhatsApp Group. It provides the learning steps and strategies to maximize the SGP performance. It is not merely presenting the topics, but they also should be creative to live up to the online learning atmosphere. This study is qualitative research and the data were collected from SGP activities in WAG. Firstly, the lecturer gives the example to give the presentations online through WAG such as warming up, brainstorming, main-course, cooling down, giving quote of the day (QOTD), and then closing. Furthermore, the team made presentations alternately at each meeting according to the lecturer's presentation model in several meetings. It is hoped that the results of this study will give contributions and ideas for other lecturers and researchers in teaching English online via WhatsApp.